Upaya Meningkatkan Prestasi Belajar Siswa Pada Mata Pelajaran Fiqih Kelas VII A Melalui Metode Cooperative Make A Match di Mts Ma’arif Munggung Ponorogo - Farid Zainul Mustofa (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2021)
In the 2013 curriculum, thematic learning is conceptualized with other learning so that it can be expected to facilitate existing learning. Through a thematic approach, teachers can relate one subject with another. This is a challenge for teachers who are familiar with mapping subjects and then switch to the concept of themes and some are still mapping. The formulation of this research problem is how to apply the Make a Match method to improve students' understanding of Thaharah's subject matter. Research methods using action research or action research is a research model that is at the same time practising and theorizing, or combining theory while implementing in practice. The result of this study is the effectiveness of the use of cooperative learning methods can increase the learning spirit of MTs student Ma'arif Munggung. This can be known by an increase in the pre-test and post-test values of the two experimental groups.